Letter and Speech Sound Association in Emerging Readers With Familial Risk of Dyslexia - Plewko, Joanna; Chyl, Katarzyna; Bola, Łukasz; Łuniewska, Magdalena; Dębska, Agnieszka; Banaszkiewicz, Anna; Wypych, Marek; Marchewka, Artur; van Atteveldt, Nienke; Jednoróg, Katarzyna (Frontiers in Human Neuroscience, 2018)
In alphabetic scripts, learning letter-sound (LS) association (i.e. letter knowledge) is a strong predictor of later reading skills. LS integration is related to left superior temporal cortex (STC) activity and its disruption was previously observed in dyslexia. Whether disruption in LS association is a cause of reading impairment or a consequence of decreased exposure to print remains unclear. Using fMRI we compared activation for letters, speech sounds and LS association in emerging readers with (FHD+, N=50) and without (FHD-, N=35) familial history of dyslexia, out of whom 17 developed dyslexia two years later. Despite having similar reading skills, FHD+ and FHD- groups showed opposite pattern of activation in left STC: In FHD- children activation was higher for incongruent compared to congruent, whereas in FHD+ it was higher for congruent LS pairs. Higher activation to congruent LS pairs was also characteristic of future dyslexia. The magnitude of incongruency effect in left STC was positively related to early reading skills, but only in FHD- children and (retrospectively) in typical readers. We show that alterations in brain activity during LS association can be detected at very early stages of reading acquisition, suggesting their causal involvement in later reading impairments. Increased response of left STC to incongruent LS pairs in FHD- group might reflect an early stage of automatizing LS associations, where the brain responds actively to conflicting pairs. The absence of such response in FHD+ children could lead to failures in suppressing incongruent information during reading acquisition, which could result in future reading problems.